Capacity spectrum of SPSW using pushover and energy method without need for calculation of target point. (August 2020) - Gholhaki, Majid; Pachideh, Ghasem; Javahertarash, Amirali
Abstract: The mass center of the roof in building frames is usually considered as a target point when a nonlinear static (pushover) analysis needs to be carried out. In the present study, 12 steel frames with 7, 15 and 30 stories as well as 5 and 7 spans equipped with steel plate shear wall (SPSW) as the lateral load-resisting system, were modeled numerically and displacement capacity spectrum was extracted based on two energy methods without need to consider the target point. In addition, two-dimensional steel frames had rigid or pinned connections and all of them were analyzed aiming to compare capacity spectra of the models including different stories. The results demonstrated that the displacement capacity spectrum obtained using the energy methods had good compatibility with each other. In conclusion, it was found that compared to the displacement capacity spectrum where the mass center of the roof was considered as a target point, there is an acceptable agreement between the displacement capacity spectrum with the target point in the first mode and displacement capacity spectrum obtained using two methods without the target point.